2015
DOI: 10.11002/kjfp.2015.22.2.218
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the quality characteristics of cricket (Gryllus bimaculatus) under various processing conditions

Abstract: Changes in the quality characteristics of cricket (Gryllus bimaculatus) under various processing conditions

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 6 publications
1
5
0
Order By: Relevance
“…). In a similar study, the chitin content of G. bimaculatus powder was 9.77, 12.25, 11.27, and 6.36 % following lyophilization, hot‐air, roasting, and frying processes, respectively (Kim et al ). In the manufacture of chitin using sodium hydroxide and oxalic acid, the yield of chitin and chitosan obtained from G. bimaculatus powder was 5.10 and 2.13 % on a DW basis, respectively (Chae ).…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…). In a similar study, the chitin content of G. bimaculatus powder was 9.77, 12.25, 11.27, and 6.36 % following lyophilization, hot‐air, roasting, and frying processes, respectively (Kim et al ). In the manufacture of chitin using sodium hydroxide and oxalic acid, the yield of chitin and chitosan obtained from G. bimaculatus powder was 5.10 and 2.13 % on a DW basis, respectively (Chae ).…”
Section: Discussionmentioning
confidence: 87%
“…Methanol extracts from G. bimaculatus display liver protection properties in mice (Ahn et al ). The quality characteristics of G. bimaculatus reported on the aspect of nutrient content including polyunsaturated fatty acids and amino acid (Kim et al ).…”
Section: Introductionmentioning
confidence: 99%
“…The results were in line with the previous study by Kim et al, which reported that the content of USFAs (60.74 ± 0.4 to 63.55 ± 0.56% w/w) was double that of SFAs (29.19 ± 0.79 to 31.88 ± 0.56% w/w) in G. bimaculatus powder from various processing conditions, including lyophilization process, hot-air process at 90 °C for 7 h, roasting process at 160 °C for 40 min, and frying process at 180 °C for 30 sec. 31 However, the results differed from the previous study by Udomsil et al, which reported that the ratio of SFAs: MUFAs: PUFAs was 12.76: 9.85: 1.80 in G. bimaculatus powder from an air-dried process at 60 °C for 48 h. 8 …”
Section: Resultsmentioning
confidence: 74%
“…However, research on these methods as applied to insect materials is currently lacking. The storage of insect products has been studied in more detail; for example, oxidation safety during the storage of rice grasshoppers, brown grasshoppers, crickets, and white spotted flower beetles has been reported (Kim et al 2015a;Kim et al 2016;Son et al 2016), as has the quality of crickets during storage (Kim et al 2016). In addition, the quality characteristics of edible crickets have been reported according to processing conditions (Lee & Kim 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The storage of insect products has been studied in more detail; for example, oxidation safety during the storage of rice grasshoppers, brown grasshoppers, crickets, and white spotted flower beetles has been reported (Kim et al . 2015a; Kim et al . 2016; Son et al .…”
Section: Introductionmentioning
confidence: 99%